H-infinity controller with graphical LMI region profile for liquid slosh suppression - Mohd Zaidi Mohd Tumari; A. Shamsul Rahimi A. Subki; Mohd Shahrieel Mohd Aras; Mohammad 'Afif Kasno; Mohd Ashraf Ahmad; Mohd Helmi Suid (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper presents a H-infinity synthesis with pole clustering based on LMI region schemes for liquid slosh control. Using LMI approach, the regional pole placement known as LMI region combined with design objective in H-infinity controller guarantee a fast input tracking capability and very minimal liquid slosh. A graphical profile of the transient response of liquid slosh suppression system with respect to pole placement is very useful in giving more flexibility to the researcher in choosing a specific LMI region. With the purpose to confirm the design of control scheme, a liquid slosh model is considered to represent the lateral slosh movement. Supremacy of the proposed approach is shown by comparing the results with hybrid model-free fuzzy-PID controller with derivative filter. The performance of the control schemes is examined in terms of time response specifications of lateral tank tracking capability and level of liquid slosh reduction.